Eficiência relativa da gestão de restos a pagar nas universidades federais no contexto do Decreto nº 9.428/2018 - Mota, Samuel Cavalcante (2021)
The implementation of the Public Spending Ceiling Law aggravated the scarcity of resources in federal universities. The budget shortage scenario requires public managers to act with a focus on efficiency. In the scope of the federal government, added to the scarcity of resources, the pressure for increased efficiency in the management of unprocessed unpaid bills, especially in relation to unprocessed unpaid bills (UUP). In this context, a relevant initiative to contain the stock of UUP was Decree No. 9,428/2018, which limited the period for execution of unprocessed unpaid bills to three years, including regarding education resources. In this context, this study aimed to analyze the relative efficiency of the management of unprocessed unpaid bills within the scope of federal universities, with the advent of Decree No. 9,428/2018. For this purpose, data envelopment analysis (DEA) was used to analyze the relative efficiency of the management of UUPs, within the scope of federal universities, from 2018 to 2020, and the Malmquist Productivity Index (DEA/IPM) was also used to identify the universities that suffered the greatest impact on their production efficiencies in the management of UUPs, in the context of the Decree. It was also used a cluster analysis to investigate the homogeneity of the groups. of universities, depending on the current cost per equivalent student (CCES), creation time and academic performance. The results indicate that, in general, federal universities did not show an increase in efficiency in the management of unpaid bills due to the implementation of Decree No. 9,428/2018, which did not impact the total productivity, from 2018 to 2020 of the UUP of capital expenditures, and in the other current expenses there is a small loss of productivity in the order of approximately 5%. When analyzed jointly, the average efficiency of capital expenditures was markedly lower than that of the group of other current expenses, only in 2019 and, in 2018 it was also lower, however, in the order of little more than 2% and in the year 2020, it was slightly higher, at approximately 0.5%. Cluster analysis allows us to state, the most numerous groups was composed of the oldest universities, with good performance in the RUF-Ranking, efficiency in the management of UUP above average and CCES below average.